Development of a decision support system for drinking water treatment process design (WATER-DSS) - Chuang, Kuang Hong (2006)
A decision support system (DDS), named WATER-DSS has been developed to assist engineers and researchers on drinking water treatment plant. The objective of WATER-DSS was to assist designers to perform process design for drinking water treatment. WATER-DSS contains two main components: (i) knowledge-based information and (ii) programming tool. The design of drinking water treatment plant in WATER-DSS depends on the characteristic of raw water and the water quality objectives. Visual Basic 6.0 was selected to develop WATER-DSS because its capability of object oriented programming. WATER-DSS has user-friendly interfacing capability, which provides the parameters inputs, standard parameters value list, raw water treatment process information, graphical and explanations features .WATER-DSS was validated by the manual calculations and has shown the relationship between WATER-DSS output and manual calculation output is significant.